Theodore Roosevelt's Ghost : The History and Memory of an American Icon - Cullinane, Michael Patrick 1979-; Cullinane, Michael Patrick 1979- (Book collections on Project MUSE., 2017)
Constructing a legacy -- Prometheus unbound -- The first monuments -- The other Roosevelt -- Cold War revival -- Unfinished business -- A second decline and revival -- An icon everlasting